Maximizing student potential: Lessons for pharmacy programs from the patient safety movement - Ephrem Abebe; Amy Bao; Peter Kokkinias; Alissa L. Russ-Jara; Dan Degnan (Exploratory Research in Clinical and Social Pharmacy, 2023)
Higher education institutions (HEIs), including pharmacy programs, are experiencing growing pressure from the public and policy makers to develop student-centered learning experiences that meet societal needs. While HEIs may have in-house initiatives to meet such challenges, there are also opportunities for cross-domain learning and application of useful concepts from other sectors. One such sector that lends itself to cross-domain learning is the healthcare industry. Like HEIs, the healthcare industry has been experiencing pressure from its stakeholders, in this case, to address patient safety gaps. These forces intensified at the turn of the century leading to the emergence of what is now known as the patient safety movement, which enabled increased advocacy, education, and research to reduce healthcare-related harm. Despite persistent challenges, a key achievement of the patient safety movement has been application of a systems framework to understand and solve patient safety gaps. That is, patient safety gaps are often a result of system defects rather than isolated acts of individual workers operating in a complex social and technical work setting (often referred to as sociotechnical system). Commonly used systems frameworks describe a sociotechnical system through its components: 1) structure (e.g., people, tools/technology, physical workspaces); 2) processes (e.g., medication administration); and 3) outcomes (e.g., medication safety, patient satisfaction). At their core, both HEIs and healthcare organizations are complex sociotechnical systems that organize their structures to support specific processes - learning in HEIs and patient safety in healthcare - to ultimately improve outcomes for students and patients, respectively. This paper describes parallels between HEIs and the healthcare domain to illustrate how patient safety concepts and practices from healthcare can be adapted to HEIs in order to enhance educational structures, processes, and learning outcomes.